Kearifan Lokal Manre Sipulung Masyarakat Bugis Petani Padi Sawah - Besse Eka Damayanti; La Ode Amaluddin; Surdin Surdin; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Bendewuta village is dominated by the Bugis tribe. The Bugis tribe in Benewuta village has local wisdom, one of which is the Manre Sipulung tradition. The aim of this research is to find out the values ​​contained in the local wisdom of Manre Sipulung, the implementation of this tradition, and the reasons why the Bugis community continues to maintain this local wisdom. The data collection method used was observation and in-depth interviews with residents of Bendewuta Village. The results of the research show that the Manre Sipulung tradition contains various cultural values, but there are three main values ​​that are highly upheld, namely Sipakatau (mutual humanization), Sipakalebbi (mutual respect), and Sipakainge (reminding each other). Implementation of this tradition includes determining the time, preparing the location, reading prayers, and eating together. The community maintains this tradition because apart from being a cultural heritage that is routinely carried out every year after the harvest, this tradition also has meaning that is relevant to current developments and reflects their fears and hopes.